Disease burden of COPD attributable to PM2.5 in China, Japan and South Korea from 1990 to 2019: a comparative study based on Global Burden of Disease Study 2019 - Bei Li; Xiao-Fen Cheng; Shu-Hui Min; Rui-Qi Guo; Jin-Dan Zhang; Yi-Li Zhang (BMJ Open)
Objective We hope to reveal the changing trends of chronic obstructive pulmonary disease (COPD) burden attributable to particulate matter pollution (PM2.5) and its age, period and cohort effects in China, Japan and Korea.Design We analysed the trend of COPD disease burden attributable to PM2.5 from 1990 to 2019 based on the latest Global Burden of Disease Database (GBD 2019) using JoinPoint model and analysed the effect of age, period and cohort on COPD burden attributable to PM2.5 in China, Japan and Korea from 1990 to 2019 using age-period-cohort model (model).Setting GBD data from 1990 to 2019.Participants Data were publicly available and individuals were not involved.Main outcomes Outcomes included the age standardised mortality rate (ASMR), the age-standardised disability-adjusted life year (DALY), average annual per cent change (AAPC), net drift, local drift, longitudinal age curves, period (cohort) rate ratios, age (period, cohort) bias coefficient.Results From 1990 to 2019, the ASMR of COPD attributable to PM2.5 in China (AAPC=−5.862), Japan (AAPC=−1.715) and Korea (AAPC=−1.831) showed a downward trend. The age-standardised DALY of COPD attributable to PM2.5 in China (AAPC=−5.821), Japan (AAPC=−1.39) and Korea (AAPC=−1.239) showed a downward trend. Mortality of COPD attributable to PM2.5 increased slowly with age in Korea and Japan. Mortality of COPD attributable to PM2.5 in China decreased after rising (95% CI: 404.66 to 466.01). Mortality of COPD attributable to PM2.5 decreased over time in China and Korea, while it increased in Japan from 2015 to 2019. In China and Japan, mortality of COPD attributable to PM2.5 was approximately lower the later the birth, while in Korea it decreased after an increase (95% CI: 2.13 to 2.40) in the 1900–1910.Conclusions Most COPD burden attributable to PM2.5 is on the decline; COPD mortality attributable to PM2.5 both increased with age and decreased with time and cohort. Countries with high burden should develop targeted measures to control PM2.5.